National Culture and the Stream Analogy of Lethal Violence - Chon, Donsoo (Homicide studies, 2023)
This is the first study to explore the relationship between Inglehart and Baker’s national cultural measures and the stream analogy of lethal violence. Using data for 70 developed and developing countries, the regression analysis indicates that a country with self-expressionism or secularism is likely to have a high suicide rate relative to its homicide rate. In contrast, a country with a survivalism or traditionalism orientation is likely to have a high homicide rate relative to its suicide rate. This study suggests that national culture is related to the direction of lethal violence (i.e., suicide vs. homicide).